A methodological approach to the design of optimising control strategies for sewer systems. (September 2016) - Mollerup, Ane Loft; Mikkelsen, Peter Steen; Sin, Gürkan
Abstract: This study focuses on designing an optimisation based control for sewer system in a methodological way and linking it to a regulatory control. Optimisation based design is found to depend on proper choice of a model, formulation of objective function and tuning of optimisation parameters. Accordingly, two novel optimisation configurations are developed, where the optimisation either acts on the actuators or acts on the regulatory control layer. These two optimisation designs are evaluated on a sub-catchment of the sewer system in Copenhagen, and found to perform better than the existing control; a rule based expert system. On the other hand, compared with a regulatory control technique designed earlier in Mollerup et al. (2015), the optimisation showed similar performance with respect to minimising overflow volume. Hence for operation of small sewer systems, regulatory control strategies can offer promising potential and should be considered along more advanced strategies when identifying novel solutions. Highlights: A methodology for hierarchical design of control and optimisation for sewer systems. Systematic evaluation of optimisation based sewer system control on a case study. Benchmarking of optimisation parameters. Comparison of optimisation based control and regulatory control. Two novel control solutions are found that outperform the existing control system.